increase of the flower-visit by Apis mellifera L. (Hymenoptera: Apidae) in crops by the use of the synthetic Nasonov pheromone - PARDO-P., RAUL; NATES-P., GIOMAR (Revista Colombiana de Entomología, 1994)
The aim of this study was to determine whether the application of the synthetic Nasonov pheromone could increase the number of flower-visits by the honey bee Apis mellifera, and consequently improve crop pollination. Initially, the attraction-power of most of the pheromone individual components (Neral, Nerol, (Z,E) Citral, Geraniol, and Geranic and Nerolic acids) was tested. First, the bees were trained to visit an artificial food source (two Petri dishes containing 50% sucrose). Then, the food in one petri dish was replaced by filter paper impregnated with the component to be tested, while the other remained as a control. The number of bees visiting each dish was recorded. Based on the results obtained, a mixture of the components was prepared and tested in a strawberry field. A greenhouse was built into the field and divided into four plots of 9 m’, with a beehive in the center. The pheromone was applied to two of the plots and the others served as controls. The number of visits to the flowers was then recorded. The most attractive components of the Nasonov pheromone were: Nerol (200 pg), Neral (50 pg), and (Z.E) Citral (100 lag). Geraniol, and Geranic and Nerolic acids were the least attractive. The mixture of Neral: 1; (Z,E) Citral: 2; Nerol: 4; Geraniol: 2; and Geranic and Nerolic acids: 2; proved to be more attractive than anyone of the individual components alone, and when this mixture was spread over the strawberry field, the number of flower visits increased. These results suggest that the Nasonov pheromone could be used to attract honeybees and thus improve pollination and crop productivity.